The Role of the Hashemite Leadership in the Development of Human Resources in Jordan: An Analytical Study - Al-Khasawneh, Akif Lutfi; Barakat, Hamdi Jaber (International Review of Management and Marketing, 2016)
The study aimed at identifying the successive role of the Hashemite leadership in Jordan in terms of developing human resource, also identifying the development areas of human resource development, which has been a focus by the successive Hashemite leadership in Jordan. The study used the qualitative approach by using an analytical historical methodology as well as inductive and deductive approach. The study population consists of the Hashemite leaders (kings), who succeeded to the throne of Jordan. The study highlighted the following findings: Emphasis on the need to empower all working Jordanians in various business sectors in the Kingdom of Jordan which will reflect their performance. The Hashemite leadership keeps urging governments and local institutions to achieve various equal opportunities for all members of the Jordanian society and get away from the two plagues cronyism and nepotism in order to tackle the problem of unemployment and provide job opportunities for Jordanian youth. Focusing on applying the principle of justice and equality among all segments of the society regardless of religions and races as well as guarantee their rights and needs in terms of jobs, health and education services and much more. Ongoing support for education, health and social security. Activating the role of professional and labor unions to contribute to provide the best services for workers and protect their rights. Keywords: the Hashemite leadership, human resources, Jordan. JEL Classification: O15